Visual pollution in Bogota: analysis of visual load in locations with high advertising stimulation - Arango, Carlos Andrés; Rodríguez-Martínez, Guillermo; Marroquín-Ciendúa, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The visual contamination is defined as a perceptual effect composed of disorder and excess of images within the visual field. This study was aimed at establishing visual load levels manifested in 13 urban landscapes of Bogotá City (Colombia). We wanted to establish levels of association between the different variables that contribute to visual load indexes (ViLI), as well as the difference that exists between the visual contamination detected in two different planes of the visual field (one lower and one higher) in relation to the observers´vertical visual horopter. 130 people participated in the study. To define the levels of visual load, the reticulum tracing methodology was implemented on photographs that emulate the arrangement of visual stimuli into the retinal image. It is concluded that the visual load is greater when the objects are at the level or below 15 ° in the visual field. Although visual stimuli that are above 15° provide visual load, they imply a significantly lower index of visual contamination.